ANALISIS BEBAN KERJA SATUAN POLISI PAMONG PRAJA (SATPOL PP) KOTA PEKANBARU - Fadilatul A Fatmawati; Dadang Mashur (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Division of tasks within an organization is important because it can affect the results of the performance of an organization are the same as the unit of Polis Pamong Praja Kora the weekend's new Division of labor, working hours, hours of operation already in the field Please specify in order to produce quality employees and quantity. The question of quality, quantity and availability of a number of agencies also issue, number of apparatus which are limited and not balanced with the workload of each employee fits the responsibilities in the gariskan organizational unit of the Pamong Praja police. It is each of the predefined target volume of work is reached. This research issue is how the police workload analysis of Pamong Praja (Satpol PP) town of Pekanbaru. the purpose of this research is to analyze the workload of police Pamong Praja (Satpol PP) town of Pekanbaru and to analyse what factors affect the workload of the police unit of Pamong Praja (Satpol PP) town of Pekanbaru. the concept of theory used in the study is the analysis of the workload by Moekijat (2008) which starts from the calculation of the effective working time, the time of completion of the tasks, and the needs of employees. This research uses descriptive qualitative research methods. In this study researchers using the technique of observation and interviews. The results of this research resulted in the conclusion that the police have a number of Municipal Teachers ' workload is 1,516 hours per year. It is above the total productive time for CIVIL SERVANTS i.e. 1,440 hours per year. Thus it can be concluded that the number of workload and availability of Pamong Praja Police manpower is not balanced. There are several factors that affect the workload of police Unit (Satpol PP) Pekanbaru city, namely: motivation, motivation owned by Satpol PP Personi must be able to move, direct and sustain the individual determination to provide the best results of a completed task. Budget workloads, attitudes displayed by personnel or groups of people will reflect the perception they have. Job satisfaction, research conducted, the average personnel of Satpol PP feel quite comfortable in carrying out the task charged. Attitude towards the task, in performing the task, the relationship between fellow personnel Satpol PP is very guarded. This is the type of task provided requires a different technique in its completion. Working organization, Satpol PP work system is not shift based, but the workload given often the time that the Satpol PP is deficient in downtime. Keywords: Workload Analysis, Satpol PP